1997
DOI: 10.1097/00001756-199704140-00039
|View full text |Cite
|
Sign up to set email alerts
|

A β42 is the predominant form of amyloid b -protein in the brains of short-term survivors of head injury

Abstract: Fatal head injury results in the formation of diffuse parenchymal deposits of amyloid beta-protein (A beta) in the brains of approximately 30% of individuals. We used carboxyl terminal-specific antisera to examine the exact nature of these deposits in paraffin sections of neocortex from seven head-injured patients. Immunostaining for A beta 42 was observed in all parenchymal deposits whereas staining for A beta 40, the form of the protein which predominates in serum and cerebrospinal fluid, was seen in only a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(59 citation statements)
references
References 4 publications
1
58
0
Order By: Relevance
“…In fact, a recent study using the carbon 11-labeled Pittsburgh Compound B positron emission tomography ligand demonstrated deposition of Aβ in cortical gray matter and striatum in patients with head injury followed for 1 year after TBI [53]. The predominant amyloid identified has been Aβ 1-42 [54,55], the most toxic form of this peptide [56][57][58]. Others have demonstrated elevated expression of the amyloid precursor protein in cortex from hours to years after TBI [59][60][61][62].…”
Section: Mechanistic Associationsmentioning
confidence: 99%
“…In fact, a recent study using the carbon 11-labeled Pittsburgh Compound B positron emission tomography ligand demonstrated deposition of Aβ in cortical gray matter and striatum in patients with head injury followed for 1 year after TBI [53]. The predominant amyloid identified has been Aβ 1-42 [54,55], the most toxic form of this peptide [56][57][58]. Others have demonstrated elevated expression of the amyloid precursor protein in cortex from hours to years after TBI [59][60][61][62].…”
Section: Mechanistic Associationsmentioning
confidence: 99%
“…21 Even a single TBI may be associated with ab42 deposits in the postmortem brains of short-term (6 h to 7 days) or long-term (1-47 years) TBI survivors. 22,23 Further, positron emission tomography studies using carbon 11-labeled Pittsburgh Compound B ([ 11 C]PiB) showed increased amyloid deposition following acute TBI compared to controls. 24 Simoa is a novel technology that employs highly sensitive immunoassays and allows accurate measurements of candidate biomarkers found at low concentrations in blood.…”
mentioning
confidence: 99%
“…2). As a support to this concept it has been shown that temporary hypoxia or energy deprivation is able to generate ß-amyloid without cognitive defects [40,88,89] in young adults following a sustained hypoxic coma or traumatic brain lesions [90,91].…”
Section: Atp and ßApp Processingmentioning
confidence: 99%